Antidiabetic, Antioxidative and Antihyperlipidemic Effects of Strawberry Fruit Extract in Alloxan-Induced Diabetic Rats - Iftikhar Younis Mallhi; Muhammad Sohaib; Azmat Ullah Khan; Imtiaz Rabbani (Foods, 2023)
Strawberry (Fragaria × ananassa) is one of the accomplished sources of bioactive compounds, including anthocyanin, phenolic acids, flavonols, ellagitannins, and a diverse range of minerals and vitamins that can help to boost human health. This study was carried out to explore the antidiabetic, antioxidative and antihyperlipidemic potential of strawberry extracts against alloxan-induced (100 mg/kg body weight) diabetic rats. Accordingly, rats were categorized into six groups including control (G0), positive control (G1), treatment groups (G2, G3, and G4) given strawberry extract at 250, 500, and 750 mg/kg of body weight, respectively, and G5 provided metformin @70 mg/kg BW for 28 days with ad libitum diet. At the trial termination, the rats were sacrificed and were subjected to analysis including body weight, blood glucose level and glycemic indicators, antioxidant parameters, lipid profile, renal function test (RFT), liver function test (LFT) and histopathology for pancreatic tissues. The results indicated that treatment of diabetic rats with strawberry extract at 500 mg/kg body weight (BW) resulted in significant reductions in blood glucose level, serum urea, and creatinine as well as significant increases in body weight, insulin activity, and protein levels. In addition, the diabetic rats that did not receive strawberry extract (control) exhibited an increase in plasma glucose, urea, uric acid, creatinine, and a decrease in body weight and insulin levels. Briefly, it is reported that strawberry fruit extracts reduced blood sugar levels, possess hypolipidemic potential, and helped to maintain antioxidant levels in alloxan-induced diabetic rats.